Chromatin fiber structural motifs as regulatory hubs of genome function?. Issue 1 (9th April 2019) - Moraru, Manuela; Schalch, Thomas
Abstract : Nucleosomes cover eukaryotic genomes like beads on a string and play a central role in regulating genome function. Isolated strings of nucleosomes have the potential to compact and form higher order chromatin structures, such as the well-characterized 30-nm fiber. However, despite tremendous advances in observing chromatin fibers in situ it has not been possible to confirm that regularly ordered fibers represent a prevalent structural level in the folding of chromosomes. Instead, it appears that folding at a larger scale than the nucleosome involves a variety of random structures with fractal characteristics. Nevertheless, recent progress provides evidence for the existence of structural motifs in chromatin fibers, potentially localized to strategic sites in the genome. Here we review the current understanding of chromatin fiber folding and the emerging roles that oligonucleosomal motifs play in the regulation of genome function.